Questions about STDP as a General Model of Synaptic Plasticity - Lisman, John; Spruston, Nelson (Frontiers in Synaptic Neuroscience, 2010)
According to spike-timing-dependent plasticity (STDP), the timing of the Na+ spike relative to the EPSP determines whether LTP or LTD will occur. Here, we review our reservations about STDP. Most investigations of this process have been done under conditions in which the spike is evoked by postsynaptic current injection. Under more realistic conditions, in which the spike is evoked by the EPSP, the results do not generally support STDP. For instance, low-frequency stimulation of a group of synapses can cause LTD, not the LTP predicted by the pre-before-post sequence in STDP; this is true regardless of whether or not the EPSP is large enough to produce a Na+ spike. With stronger or more frequent stimulation, LTP can be induced by the same pre-before-post timing, but in this case block of Na+ spikes does not necessarily prevent LTP induction. Thus, Na+ spikes may facilitate LTP and/or LTD under some conditions, but they are not necessary, a finding consistent with their small size relative to the EPSP in many parts of pyramidal cell dendrites. The nature of the dendritic depolarizing events that control bidirectional plasticity is of central importance to understanding neural function. There are several candidates, including backpropagating action potentials, but also dendritic Ca2+ spikes, the AMPA receptor-mediated EPSP, and NMDA receptor-mediated EPSPs or spikes. These often appear to be more important than the Na+ spike in providing the depolarization necessary for plasticity. We thus feel that it is premature to accept STDP-like processes as the major determinant of LTP/LTD.